AfricanAmericanWomenandtheCivilRightsMovementinthe1960s - BouguettayaLouiza, DebbihZineb (My University, 2019)
Abstract: AlthoughslaverywasabolishedintheUSaftertheendoftheCivilWar(1861-1865)andAfricanAmericansgainedsomelegalstatus,racialsegregationknownasJimCrowaroseintheSouth.Thetermmeant,generally,thatSouthernblackswouldcontinuetoliveinconditionsofpovertyandinequality,whilewhitesupremacistsdeniedtheirpoliticalrightsandfreedoms.African AmericanstruggleisbestknownintheUShistoryastheCivilRightMovementduringwhichAfricanAmericans,bothmenandwomen,determinedtoachievetherightsandprerogativesoffullcitizenship,emphasizingliberty,justice,andequality.InthehistoryofCivilRightMovement,menlikeDr.MartinLutherKingandMalcomXaregenerallyreferredtoasheroeswhofoughtracialsegregation.However,thefiguresofAfricanAmericanwomenactivistssuchasEllaBaker,DianeNash,FannieLouHamer,AnnieLeeCooper,andAngelaDavisstillarelessmentionedinthecivilrightsmovement;althoughtheyroseasbrilliantactivistsinthemovementandparticipatedheavilyinthestruggleforjusticeandequality.ThepresentresearchhighlightsAfricanAmericanwomen’sinvolvementintheCivilRightsMovementtofightfortheirrights,andwhatweretheirachievements.
Keywords: Keywords:Civilrightsmovement,AfricanAmericanwomen,racialsegregation.